Introducing the Banishment Stele into the 20th Dynasty - Thijs, Ad (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
This article deals with the consequences of dating the Banishment Stele (Louvre C. 256) to the period immediately following the suppression of the High Priest of Amun, Amenhotep. It is postulated that the suppression was ended by a coalition of Ramses XI Menmare with Psusennes I, normally thought to have reigned much later. The latter sent his general/High Priest, Menkheperre, who temporarily took over the Theban high priesthood but had to withdraw when Amenhotep returned from exile. When order was restored, a new era was proclaimed: the wHm mswt . The lower date on the stele is interpreted as year 1 of this era, allowing the stele’s year 25 to become part of the 48-year reign of Psusennes I. It is shown how the events described in the Banishment Stele ultimately led to the political compromise that was the Oracle of Herihor (see: ZÄS 132): Ramses XI was not succeeded by Herihor, but by a king whose name (Khakheperre Pinuzem) suggests links with both Akheperre Psusennes I and HPA Menkheperre.